Layered MoS2 Grown on Anatase TiO2 {001} Promoting Interfacial Electron Transfer to Enhance Photocatalytic Evolution of H2 From H2S - Cai, Qing; Wang, Fang; Xiang, Jianglai; Dan, Meng; Yu, Shan; Zhou, Ying (Frontiers in Environmental Chemistry, 2020)
The treatment of hazardous hydrogen sulfide (H2S) via photocatalysis technology has been known as one of the most promising green technologies. Photocatalytic production of hydrogen (H2) from H2S by two-dimensional (2D) semiconductor materials has gathered great attention owing to its large surface area and high catalytic activity. In this work, layered MoS2 has been successfully grown on TiO2 {001} surface to fabricate the 2D MoS2/TiO2 {001} composites for H2 evolution from H2S, which can be confirmed by the X-ray diffraction (XRD) and transmission electron microscopy (TEM) tests. Band structures and UV-Vis spectra provide important evidences that MoS2 loading can significantly narrow the band gap and broaden the light absorbance into the visible light region. Electron transfer is obviously visualized at the interface of MoS2/TiO2, resulting in the built-in potential from TiO2 to MoS2, which is determined by the density functional theory (DFT) calculations and X-ray photoelectron spectroscopy (XPS) test. Consequently, the photo-induced electrons and holes are accumulated at the sides of TiO2 and MoS2 under the illumination, respectively, which largely promote the interfacial electron transfer and prolong the lifetime of photo-generated electrons that participate in the photocatlytic reactions of H2 evolution from H2S. This efficient separation of photo-induced carriers can be further proved by photoluminescence (PL) spectra, photocurrent responses and electrochemical impedance spectra. As a result, the photocatlytic activity of H2 evolution is largely increased by 9.4 times compared to the pristine TiO2. This study could offer a new and facile way to design highly efficient 2D photocatalysts for the application of H2S treatment.